Analysis of back-gate effect on threshold voltage of p-channel GaN MOSFETs on polarization-junction substrates. (22nd May 2019) - Hoshii, Takuya; Nakajima, Akira; Nishizawa, Shin-ichi; Ohashi, Hiromichi; Kakushima, Kuniyuki; Wakabayashi, Hitoshi; Tsutsui, Kazuo
Abstract: GaN-based p-channel devices using a two-dimensional hole gas are of interest for the realization of GaN CMOS circuits, and threshold voltage control using a back-gate is useful for the circuit design of these devices. In this paper, the back-gate effect on p-channel GaN MOSFETs on polarization-junction substrates is studied. The results show that the obtained dependence of the threshold voltage on the back-gate voltage can be derived by a model equation considering the back surface channel. Also, by comparing the measured characteristics with the simulation result under ideal conditions, it is found that the amount of interfacial charges can be quantitatively evaluated for the fabricated device.